Answer:
12 units
Step-by-step explanation:
Given that :
R(-3,2)
S(2,2)
T(2,-5).
The total length ;
Distance between two points : √[(x2 - x1)² + (y2 - y1)²]
Distance between R and S :
R = (-3,2)
S(2,2)
√[((2 - (-3))^2 + (2 - 2)^2]
Sqrt(5^2 + 0^2)
D1 = 5 units
Distance between S and T:
S(2,2)
T(2,-5).
D2 = √[(2 - 2)^2 + (-5 - 2)^2]
D2 = sqrt(0^2 + (-7)^2)
D2 = 7 units
Hence, total length = D1 + D2 = (5 + 7) = 12 units
Answer:
89
Step-by-step explanation:
i think
Divide 636 / 12 which equals 53 ?
No they are not! If you multiply 3/4 times 4 to get the denominator as 12, you would get 9/12 which is not equivalent